Reliability of mechanical sprint profiles in state U16 female basketball athletes - Edwards, T.; Joseph, J.; Lewis, B.; Cripps, A. (Journal of Australian Strength and Conditioning, 2019)
Mechanical sprint characteristics produce acceptable trial to trial reliability in state U16 female basketball athletes.